KAMAN Protocol for Preventing Virtual Side Channel Attacks in Cloud Environment - Hardeep Kaur; Manjit Kaur (Institute of Advanced Engineering and Science, 2015)
Now’s a day cloud computing is widely accepted all around the world used for public utilities and on demand computing services. It provides lots of benefits like storage, easy access to system anytime, broad network access, resource pooling etc. Various attacks can be performed by attackers or intruder due to its large emergence. In these days security and privacy of user’s data is main concern. An attacker can access and analyse the data of users by penetrating in the cloud by different approaches. An unintelligent cloud service provider or cloud resource management can significantly increases the leakage of the information of the users. In this paper virtual side channel attack is described where attacker hijack all the credential of authorized user and access his data. A proposed solution is provided to isolate the attack. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.8088